A Photovoice Study Representing Pre-practicum EFL Student Teachers' Emotion and Identity Construction - Fauziah Fauziah; Jamaliah Jamaliah; Novita Diana (GLENS: Global English Insights Journal, 2026)
Teacher education generally aims to shape student teachers’ (STs) awareness of the teaching profession as a dynamic process through which they construct their professional identities as learners and future teachers. This study explores STs’ emotions and identity construction through the use of a photovoice-based approach as a reflective and participatory research method. Data were collected from STs (n=13) enrolled in an English language teacher education program, who documented their lived experiences through photographs and reflective narratives, supplemented by semi-structured interviews. This study follows Wang’s (1999) photovoice framework, which emphasizes participant-driven image production, critical reflection, and collective meaning-making. Trustworthiness was ensured through triangulation of photovoice and interview data, transparent analytic procedures, and grounding interpretations in participants’ narratives. The findings reveal that visual narrative (photovoice) serves as a powerful medium for articulating complex emotional landscapes encompassing a range of positive and negative emotions. Participants’ evolving professional identities are shaped by social interactions, institutional expectations, and personal beliefs about teaching, intertwined with their emotions. Participants' evolving professional identities, shaped by social interactions, institutional expectations, and personal beliefs about teaching, were found to be deeply intertwined with their emotions. This study highlights the methodological and pedagogical value of photovoice in teacher education.